Composite resin for solvent method prepreg production and preparation method thereof
Patent Information
- Application Number
- CN202510800303.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-06-16
AI Technical Summary
然而,目前产业化的热塑性树脂在常规溶剂中难以溶解,多采用熔融浸渍法制备预浸料,但熔融后熔体粘度较大,容易导致增强纤维预浸不充分,产品表面有空隙等问题;同时在一些特殊应用工况中也有进一步提升冲击韧性的需要
[0046]1)本发明采用了低分子量改性无定型聚芳醚酮和高分子量改性无定型聚芳醚酮复合体系,利用低分子量改性无定型聚芳醚酮易溶解性,在保证纤维浸润充分的前提下,还能提高预浸料溶液的固含量,提升预浸料树脂含量的稳定性;同时低分子量改性无定型聚芳醚酮与高分子量改性无定型聚芳醚酮具有相似的分子结构,能形成比较好的相互缠结,提高界面性能。
Smart Images

Figure BDA0005451065080000161 
Figure BDA0005451065080000171
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a composite resin for solvent-based prepreg production and its preparation method. Background Technology
[0002] Compared to thermosetting resin-based composites, thermoplastic resin-based composites offer advantages such as better toughness, longer prepreg shelf life, shorter molding cycles, and ease of repair; they are widely used in aerospace, automotive, sporting goods, 3C (computers, communications, and consumer electronics) and other fields. With the development of the aerospace industry, the need for weight reduction and improved overall performance in equipment is becoming increasingly urgent, placing higher demands on the mechanical properties, heat resistance, and environmental resistance of resin-based composites. Traditional general-purpose plastics and engineering plastics can no longer meet the requirements of operating conditions, while specialty engineering plastic thermoplastic resin-based composites, represented by polyetherimide (PEI), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), are widely used in the aerospace field due to their superior performance.
[0003] These types of specialty engineering plastic thermoplastic resin-based composites are mostly processed by preparing prepregs using the preimpregnation method, followed by the preparation of the thermoplastic composite. However, currently commercially available thermoplastic resins are difficult to dissolve in conventional solvents, and melt impregnation is often used to prepare prepregs. However, the high viscosity of the melt after melting can easily lead to insufficient preimpregnation of reinforcing fibers and voids on the product surface. Furthermore, there is a need to further improve impact toughness in some special applications. Therefore, developing a composite resin for the production of thermoplastic prepregs that is easily soluble in solvents and possesses high toughness is of great significance. Summary of the Invention
[0004] To overcome the above-mentioned shortcomings, the present invention aims to provide a composite resin for solvent-based prepreg production, which can improve the tensile strength and toughness of prepreg.
[0005] To achieve the above objectives, the technical solution adopted by this invention is: a composite resin for solvent-based prepreg production, wherein the raw materials for preparing the composite resin, by weight, include:
[0006] 35-145 parts of modified amorphous polyaryletherketone;
[0007] 8-35 parts polycarbonate;
[0008] 0.5-6 parts of modified inorganic nanomaterials;
[0009] Antioxidant 0.1-0.3 parts;
[0010] Preferably, the raw materials for preparing the composite resin include: 42-130 parts of modified amorphous polyarylether ketone, 12-30 parts of polycarbonate, 1.5-4.5 parts of modified inorganic nanomaterials, and 0.1-0.3 parts of antioxidant.
[0011] Among them, the molecular structure of modified amorphous polyarylether ketone has long alkyl chain end groups, monocyano side chains, and aminosiloxane-modified amide side chains.
[0012] Furthermore, modified amorphous polyarylether ketones include high molecular weight modified amorphous polyarylether ketones and low molecular weight modified amorphous polyarylether ketones.
[0013] Furthermore, the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 3-30:1.
[0014] For example, the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is a range of 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, or any combination thereof.
[0015] Preferably, the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 6-15:1.
[0016] Furthermore, the average molecular weight of high molecular weight modified amorphous polyarylether ketone is 20,000-40,000; the average molecular weight of low molecular weight modified amorphous polyarylether ketone is 5,000-10,000.
[0017] Furthermore, the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 2-6:1. For example, the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 2:1, 3:1, 4:1, 5:1, 6:1, or any combination thereof.
[0018] Preferably, the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 3-4:1.
[0019] Furthermore, the preparation method of modified amorphous polyarylether ketone is as follows:
[0020] Step (1): Add the side chain agent to the phenolphthalein monomer, heat to 160-200℃ and react for 30-60 h to obtain modified phenolphthalein.
[0021] Step (2): Add modified phenolphthalein, phenolphthalein monomer, 2,6-dichlorobenzonitrile, sulfolane, anhydrous potassium carbonate, and xylene to a reaction vessel, heat to 140-160℃ and hold at that temperature for 3-5 hours, then continue heating to 200-220℃ and react for 6-10 hours to obtain a viscous polymer product.
[0022] Step (3): Add haloalkanes to the product obtained in step (2), heat to 190-210℃, stir for 1.5-3h, purify, and obtain modified amorphous polyarylether ketone.
[0023] Further, the side chain agent in step (1) is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, diaminopropylpolydimethylsiloxane, and aminopropyl-terminated polydimethylsiloxane.
[0024] Furthermore, in step (1), the mass ratio of phenolphthalein monomer to side chain agent is 1:1.5-3.
[0025] Furthermore, the amounts of each substance used in steps (2) and (3) are as follows: 260-300 parts of phenolphthalein monomer, 50-130 parts of modified phenolphthalein, 140-200 parts of 2,6-dichlorobenzonitrile, 1-13 parts of halogenated hydrocarbon, 800-1300 parts of sulfolane, 120-290 parts of anhydrous potassium carbonate, and 20-100 parts of xylene.
[0026] Furthermore, the modified phenolphthalein accounts for 10-30% of the total mass of the phenolphthalein monomer and the modified phenolphthalein.
[0027] Furthermore, the alkyl chain length of the haloalkane is C7-C10.
[0028] Preferably, the halohydrocarbon is selected from at least one of 1-chlorohexane, 1-chloroheptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane.
[0029] Furthermore, the mass ratio of the haloalkane to 2,6-dichlorobenzonitrile is 0.04-0.06:1.
[0030] Furthermore, the modified inorganic nanomaterial is a pretreated inorganic powder modified with a silane coupling agent.
[0031] Furthermore, the silane coupling agent is at least one of KH550, KH560, and KH570.
[0032] Furthermore, the pretreated inorganic powder is the product obtained by activating inorganic powder at 300-600℃ for 3-7 hours.
[0033] Furthermore, the inorganic powder is at least one of silica, montmorillonite, bentonite, and kaolinite.
[0034] Furthermore, the mass ratio of silane coupling agent to pretreated inorganic powder is 1:20-30.
[0035] Furthermore, the preparation method of modified inorganic nanomaterials includes the following steps: placing pretreated inorganic powder and silane coupling agent in toluene, ultrasonically dispersing for 5-15 min, refluxing at 100-120℃ for 2-4 h, followed by cooling, centrifugation, washing, and drying to obtain modified inorganic nanomaterials.
[0036] Furthermore, the antioxidant is at least one of antioxidant 1010 and antioxidant 168.
[0037] Furthermore, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168.
[0038] Furthermore, in the antioxidant, the mass ratio of antioxidant 1010 to antioxidant 168 is 1:(0.8-1.2).
[0039] A method for preparing a composite resin for producing the above-mentioned solvent-based prepreg includes the following steps:
[0040] S1. Mix high molecular weight modified amorphous polyaryletherketone, low molecular weight modified amorphous polyaryletherketone, polycarbonate, modified inorganic nanomaterials, and antioxidant evenly to obtain a mixture;
[0041] S2. Add the mixture to a twin-screw extruder, extrude and granulate to obtain modified particles;
[0042] S3. The modified particles are cryogenically pulverized to a particle size of 50-100 μm to obtain a composite resin.
[0043] Furthermore, in step S2, granulation is performed by extrusion at 200-310°C.
[0044] Furthermore, in step S3, the freezing temperature is -120℃ to -80℃.
[0045] The beneficial effects of this invention are:
[0046] 1) This invention employs a composite system of low molecular weight modified amorphous polyaryletherketone (POP) and high molecular weight modified POP. Utilizing the easy solubility of low molecular weight modified POP, it can increase the solid content of the prepreg solution and improve the stability of the prepreg resin content while ensuring sufficient fiber impregnation. At the same time, low molecular weight modified POP and high molecular weight modified POP have similar molecular structures, which can form good mutual entanglement and improve interfacial performance.
[0047] By utilizing the high specific surface area and surface energy of modified inorganic nanomaterials, which can form physical anchoring points at the polymer interface, the interfacial compatibility between polycarbonate and modified amorphous polyaryletherketone is improved. While ensuring the heat resistance and tensile strength of the blended modified resin, the toughness of the blended modified resin is further enhanced. This can significantly improve the toughness and impact resistance of composite materials, meeting the requirements of high-strength and high-toughness composite materials for components in aerospace, new energy vehicles, and rail transportation.
[0048] 2) This invention uses modified amorphous polyaryletherketone resin, introducing aminosiloxane-modified amide ring large side groups on the amorphous polyaryletherketone molecular chain. While ensuring heat resistance, it can also increase free volume and improve the flexibility of molecular chain, which can significantly improve the solubility of amorphous polyaryletherketone in some polar solvents, which is beneficial to the preparation of high-performance solution prepreg.
[0049] 3) This invention uses modified amorphous polyaryletherketone resin. By introducing cyano groups and siloxane groups on the resin molecular chain, the polarity of amorphous polyaryletherketone is improved; this can enhance the bonding force between the resin matrix and reinforcing fibers, thereby improving the mechanical properties of the composite material.
[0050] 4) This invention uses flexible alkane chains on the modified amorphous polyaryletherketone molecular chain to improve the toughness of amorphous polyaryletherketone. Detailed Implementation
[0051] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0052] Unless otherwise shown or indicated in the operational embodiments, all figures used to represent the amounts, physicochemical properties, etc., of ingredients in the specification and claims are to be understood to be adjusted by the term "about" in all cases. Therefore, unless stated to the contrary, the numerical parameters listed in the foregoing specification and appended claims are approximations, and those skilled in the art can appropriately modify these approximations to obtain the desired characteristics by utilizing the teachings disclosed herein. The use of numerical ranges indicated by endpoints includes all numbers within that range and any range within that range; for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4, and 5, etc.
[0053] An embodiment of the present invention provides a method for preparing a composite resin for solvent-based prepreg production, comprising the following steps:
[0054] S1. Mix the modified amorphous polyaryletherketone, polycarbonate, modified inorganic nanomaterials, and antioxidant evenly to obtain a mixture;
[0055] In some embodiments, the molecular structure of the modified amorphous polyarylether ketone has a long alkyl chain end group, a monocyano side chain, and an aminosiloxane-modified amide side chain.
[0056] In some embodiments, the modified amorphous polyaryletherketone includes high molecular weight modified amorphous polyaryletherketone and low molecular weight modified amorphous polyaryletherketone.
[0057] In some embodiments, in step S1, the high molecular weight modified amorphous polyarylether ketone is 32-128 parts, the low molecular weight modified amorphous polyarylether ketone is 3-17 parts, the polycarbonate is 8-35 parts, the modified inorganic nanomaterial is 0.5-6 parts, and the antioxidant is 0.1-0.3 parts.
[0058] In some embodiments, in step S1, the high molecular weight modified amorphous polyarylether ketone is 37-120 parts, the low molecular weight modified amorphous polyarylether ketone is 5-10 parts, the polycarbonate is 12-30 parts, the modified inorganic nanomaterial is 1.5-4.5 parts, and the antioxidant is 0.1-0.3 parts.
[0059] In some embodiments, the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 3-30:1.
[0060] In some embodiments, the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 6-15:1.
[0061] In some embodiments, the average molecular weight of the high molecular weight modified amorphous polyarylether ketone is 20,000-40,000; the average molecular weight of the low molecular weight modified amorphous polyarylether ketone is 5,000-10,000.
[0062] In some embodiments, the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 2-6:1.
[0063] In some embodiments, the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 3-4:1.
[0064] In some embodiments, the raw materials for preparing modified amorphous polyarylether ketone include 260-300 parts of phenolphthalein monomer, 50-130 parts of modified phenolphthalein, 140-200 parts of 2,6-dichlorobenzonitrile, 1-13 parts of halogenated hydrocarbon, 800-1300 parts of sulfolane, 120-290 parts of anhydrous potassium carbonate, and 20-100 parts of xylene.
[0065] In some embodiments, the raw materials for preparing modified phenolphthalein include phenolphthalein monomer and side-chain agent, wherein the mass ratio of phenolphthalein monomer to side-chain agent is 1:1.5-3.
[0066] In some embodiments, the side-chain agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, diaminopropylpolydimethylsiloxane, and aminopropyl-terminated polydimethylsiloxane.
[0067] In some embodiments, the modified phenolphthalein accounts for 10-30% of the sum of the mass of the phenolphthalein monomer and the modified phenolphthalein.
[0068] In some embodiments, the alkyl chain length of the haloalkane is C7-C10.
[0069] In some embodiments, the haloalkane is selected from at least one of 1-chlorohexane, 1-chloroheptane, 1-chlorooctane, 1-chlorononane, and 1-chlorodecane.
[0070] In some embodiments, the mass ratio of the haloalkane to 2,6-dichlorobenzonitrile is 0.04-0.06:1.
[0071] In some embodiments, the preparation method of modified amorphous polyarylether ketone includes the following steps:
[0072] Step (1): Add the side chain agent to the phenolphthalein monomer, heat to 160-200℃ and react for 30-60 h to obtain modified phenolphthalein.
[0073] Step (2): Add phenolphthalein, modified phenolphthalein, 2,6-dichlorobenzonitrile, sulfolane, anhydrous potassium carbonate, and xylene to a reaction vessel, heat to 140-160℃ and hold at that temperature for 3-5 hours, then continue heating to 200-220℃ and react for 6-10 hours to obtain a viscous polymer product.
[0074] Step (3): Add a haloalkane to the viscous polymer product obtained in step (2), heat to 190-210℃, stir for 1.5-3h, purify, and obtain modified amorphous polyarylether ketone.
[0075] In some embodiments, the modified inorganic nanomaterial is a pretreated inorganic powder modified with a silane coupling agent.
[0076] In some embodiments, the silane coupling agent is at least one of KH550, KH560, and KH570.
[0077] In some embodiments, the pretreated inorganic powder is the product obtained by activating inorganic powder at 300-600°C for 3-7 hours.
[0078] In some embodiments, the inorganic powder is at least one of silica, montmorillonite, bentonite, and kaolinite.
[0079] In some embodiments, the mass ratio of silane coupling agent to pretreated inorganic powder is 1:20-30.
[0080] In some embodiments, the preparation method of modified inorganic nanomaterials includes the following steps: placing pretreated inorganic powder and silane coupling agent in toluene, ultrasonically dispersing for 5-15 min, refluxing at 100-120℃ for 2-4 h, followed by cooling, centrifugation, washing, and drying to obtain modified inorganic nanomaterials.
[0081] In some embodiments, the antioxidant is at least one of antioxidant 1010 and antioxidant 168.
[0082] In some embodiments, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168.
[0083] In some embodiments, the mass ratio of antioxidant 1010 to antioxidant 168 is 1:(0.8-1.2).
[0084] S2. Add the mixture to a twin-screw extruder and extrude and granulate it at 200-310℃ to obtain modified particles;
[0085] S3. The modified particles are freeze-pulverized at -120℃ to -80℃ until the particle size is 50-100um to obtain a composite resin.
[0086] Example
[0087] The following examples describe the disclosure of this invention in more detail. These examples are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized by conventional methods and can be used directly without further processing. The instruments used in the examples are also commercially available.
[0088] Example 1
[0089] A method for preparing a composite resin for solution-based prepreg production includes the following steps:
[0090] S1. Mix 71 parts of high molecular weight modified amorphous polyaryletherketone, 6.5 parts of low molecular weight modified amorphous polyaryletherketone, 20 parts of polycarbonate, 2.7 parts of modified inorganic nanomaterials, and 0.2 parts of antioxidant (0.1 parts of antioxidant 1010 and 0.1 parts of antioxidant 168) evenly to obtain a mixture.
[0091] S2. Add the mixture to a twin-screw extruder and extrude and granulate it using the twin-screw extruder at temperatures of 220℃, 285℃, 290℃, 295℃, 290℃, 295℃ (drill head) to obtain modified granules.
[0092] S3. The modified particles are pulverized at -100℃ at high speed to a particle size of 60μm to obtain a composite resin for solvent-based prepreg production.
[0093] The calculated mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 71:6.5 = 10.92:1.
[0094] The mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 71:20 = 3.55:1.
[0095] in:
[0096] ① A method for preparing low molecular weight modified amorphous polyarylether ketones, comprising the following steps:
[0097] Step (1): Under nitrogen protection, phenolphthalein and 3-aminopropyltrimethoxysilane were mixed evenly in a mass ratio of 1:2.4, heated to 180°C, and stirred for 45 hours. After the reaction was completed, the temperature was lowered to room temperature, ultrapure water was added to precipitate the solid, and then the solid obtained by vacuum filtration was carried out. The solid obtained by vacuum filtration was then recrystallized with ethyl acetate to obtain modified phenolphthalein.
[0098] Step (2): Add 273 parts of phenolphthalein monomer, 100 parts of modified phenolphthalein, 170 parts of 2,6-dichlorobenzonitrile, 1000 parts of sulfolane, 160 parts of anhydrous potassium carbonate, and 70 parts of xylene to a reaction vessel, heat to 150℃ and hold for 4 hours, then continue heating to 210℃ and react for 8 hours to obtain a viscous polymer product; (The molar ratio of phenolphthalein (including phenolphthalein monomer and modified phenolphthalein) to 2,6-dichlorobenzonitrile is between 1.05 and 1.07:1, which can obtain low molecular weight modified amorphous polyarylether ketones with a molecular weight of 5000-10000)
[0099] Step (3): Add 8 parts of 1-chlorooctane to the viscous polymer product obtained in step (2), stir evenly, react at 200°C for 2 hours, cool down, add 2500 parts of dimethylacetamide to dilute, and stir evenly; under vigorous stirring, pour the solution into a large amount of water to precipitate, filter and crush using a high-speed mixer; then wash the product with dilute hydrochloric acid and pure water in sequence, and dry to obtain low molecular weight modified amorphous polyarylether ketone.
[0100] The calculated ratio of the mass of modified phenolphthalein to the total mass of phenolphthalein monomer and modified phenolphthalein is: 100 / (100+273)*100%=26.8%.
[0101] ② The preparation method of high molecular weight modified amorphous polyarylether ketone is basically the same as that of low molecular weight modified amorphous polyarylether ketone, the difference being: the raw materials for preparing the viscous polymer product in step (2) include 270.3 parts phenolphthalein monomer, 99 parts modified phenolphthalein, 173.7 parts 2,6-dichlorobenzonitrile, 1000 parts sulfolane, 160 parts anhydrous potassium carbonate, and 70 parts xylene. (The molar ratio of phenolphthalein (including phenolphthalein monomer and modified phenolphthalein) to 2,6-dichlorobenzonitrile is between 1.02 and 1.04:1, which can obtain high molecular weight modified amorphous polyarylether ketone with a molecular weight of 20,000-40,000)
[0102] The calculated ratio of the mass of modified phenolphthalein to the total mass of phenolphthalein monomer and modified phenolphthalein is: 100 / (99+270.3)*100%=26.8%.
[0103] ③ A method for preparing modified inorganic nanomaterials includes the following steps: activating silica at 400℃ for 5 hours to obtain pretreated silica; then mixing silica and KH-550 silane coupling agent at a mass ratio of 25:1, placing them together in toluene that has been dehydrated by molecular sieves, ultrasonically dispersing for 10 minutes, refluxing at 110℃ for 2 hours, and then cooling; after centrifugation at 13000 r / min, precipitating, washing five times with anhydrous ethanol, and drying to obtain modified inorganic nanomaterials.
[0104] Example 2
[0105] The preparation processes of Example 2 and Example 1 are basically the same. The main difference is that the specific proportions of the raw materials for preparing the composite resin in step S1 are different. Specifically, they are: 65.5 parts of high molecular weight modified amorphous polyarylether ketone, 10 parts of low molecular weight modified amorphous polyarylether ketone, 21.8 parts of polycarbonate, 2.6 parts of modified inorganic nanomaterials, and 0.2 parts of antioxidant.
[0106] The calculated mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 65.5:10 = 6.55:1.
[0107] The mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 65.5:21.8 = 3.00:1.
[0108] Example 3
[0109] The preparation processes of Example 3 and Example 1 are basically the same. The main difference is that the specific proportions of the raw materials for preparing the composite resin in step S1 are different. Specifically, they are: 73.5 parts of high molecular weight modified amorphous polyarylether ketone, 5 parts of low molecular weight modified amorphous polyarylether ketone, 18.5 parts of polycarbonate, 2.7 parts of modified inorganic nanomaterials, and 0.2 parts of antioxidant.
[0110] The calculated mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 73.5:5 = 14.7:1.
[0111] The mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 73.5:18.5 = 3.97:1.
[0112] Example 4
[0113] The preparation processes of Example 4 and Example 1 are basically the same. The main difference is that in step S1, the raw materials for preparing the composite resin are 60 parts of high molecular weight modified amorphous polyarylether ketone and 17.5 parts of low molecular weight modified amorphous polyarylether ketone.
[0114] Calculations show that the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 60:17.5 = 3.43:1.
[0115] Example 5
[0116] The preparation processes of Example 5 and Example 1 are basically the same. The main difference is that in step S1, the raw materials for preparing the composite resin are 73 parts of high molecular weight modified amorphous polyarylether ketone and 4.5 parts of low molecular weight modified amorphous polyarylether ketone.
[0117] Calculations show that the mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone is 73:4.5 = 16.22:1.
[0118] Example 6
[0119] The preparation processes of Example 6 and Example 1 are basically the same. The main difference is that in step S1, the raw materials for preparing the composite resin are 77.5 parts of high molecular weight modified amorphous polyarylether ketone and 13.5 parts of polycarbonate.
[0120] Calculations show that the mass ratio of high molecular weight modified amorphous polyarylether ketone to polycarbonate is 77.5:13.5 = 5.74:1.
[0121] Comparative Example 1
[0122] The preparation processes of Comparative Example 1 and Example 1 are basically the same, the main difference being that in step S1, 77.5 parts of medium molecular weight modified amorphous polyarylether ketone (molecular weight between 10,000 and 20,000) are added, replacing the 71 parts of high molecular weight modified amorphous polyarylether ketone and 6.5 parts of low molecular weight modified amorphous polyarylether ketone in Example 1. The preparation method of the medium molecular weight modified amorphous polyarylether ketone is as follows:
[0123] Step (1): Under nitrogen protection, phenolphthalein and 3-aminopropyltrimethoxysilane were mixed evenly in a mass ratio of 1:2.4, heated to 180°C, and stirred for 45 hours. After the reaction was completed, the temperature was lowered to room temperature, ultrapure water was added to precipitate the solid, and then the solid obtained by vacuum filtration was carried out. The solid obtained by vacuum filtration was then recrystallized with ethyl acetate to obtain modified phenolphthalein.
[0124] Step (2): Add 271.8 parts of phenolphthalein monomer, 99.5 parts of modified phenolphthalein, 171.7 parts of 2,6-dichlorobenzonitrile, 1000 parts of sulfolane, 160 parts of anhydrous potassium carbonate, and 70 parts of xylene to a reaction vessel, heat to 150℃ and hold for 4 hours, then continue heating to 210℃ and react for 8 hours to obtain a viscous polymer product; (The molar ratio of phenolphthalein (including phenolphthalein monomer and modified phenolphthalein) to 2,6-dichlorobenzonitrile is between 1.04 and 1.05:1, which can obtain a medium molecular weight modified amorphous polyarylether ketone with a molecular weight of 10,000-20,000)
[0125] Step (3): Add 8 parts of 1-chlorooctane to the viscous polymer product obtained in step (2), stir evenly, react at 200°C for 2 hours, cool down, add 2500 parts of dimethylacetamide to dilute, and stir evenly; under vigorous stirring, pour the solution into a large amount of water to precipitate, filter and crush using a high-speed mixer; then wash the product with dilute hydrochloric acid and pure water in sequence, and dry to obtain medium molecular weight modified amorphous polyarylether ketone.
[0126] The calculated ratio of the mass of modified phenolphthalein to the total mass of phenolphthalein monomer and modified phenolphthalein is: 99.5 / (99.5+271.8)*100%=26.8%.
[0127] Comparative Example 2
[0128] The preparation processes of Comparative Example 2 and Example 1 are basically the same. The main difference is that in step S1, both the low molecular weight modified amorphous polyarylether ketone and the high molecular weight modified amorphous polyarylether ketone added are modified amorphous polyarylether ketones without aminosiloxanes. The preparation methods of the two are as follows:
[0129] ① A method for preparing low molecular weight modified amorphous polyarylether ketones, comprising the following steps:
[0130] Step (2): Add 373 parts of phenolphthalein monomer, 170 parts of 2,6-dichlorobenzonitrile, 1000 parts of sulfolane, 160 parts of anhydrous potassium carbonate and 70 parts of xylene to a reaction vessel, heat to 150°C and keep at that temperature for 4 hours, then continue heating to 210°C and react for 8 hours to obtain a viscous polymer product.
[0131] Step (3): Add 8 parts of 1-chlorooctane to the viscous polymer product obtained in step (2), stir evenly, react at 200°C for 2 hours, cool down, add 2500 parts of dimethylacetamide to dilute, and stir evenly; under vigorous stirring, pour the solution into a large amount of water to precipitate, filter and crush using a high-speed mixer; then wash the product with dilute hydrochloric acid and pure water in sequence, and dry to obtain low molecular weight modified amorphous polyarylether ketone.
[0132] ② The preparation method of high molecular weight modified amorphous polyarylether ketone is basically the same as that of low molecular weight modified amorphous polyarylether ketone. The difference is that the raw materials for preparing the viscous polymer product in step (2) include 369.3 parts of phenolphthalein monomer, 173.7 parts of 2,6-dichlorobenzonitrile, 1000 parts of sulfolane, 160 parts of anhydrous potassium carbonate, and 70 parts of xylene.
[0133] Comparative Example 3
[0134] The preparation processes of Comparative Example 3 and Example 1 are basically the same. The main difference is that in step S1, both the low molecular weight modified amorphous polyarylether ketone and the high molecular weight modified amorphous polyarylether ketone added are modified amorphous polyarylether ketones without long-chain alkyl groups. The preparation methods of the two are as follows:
[0135] ① A method for preparing low molecular weight modified amorphous polyarylether ketones, comprising the following steps:
[0136] Step (1): Under nitrogen protection, phenolphthalein and 3-aminopropyltrimethoxysilane were mixed evenly in a mass ratio of 1:2.4, heated to 180°C, and stirred for 45 hours. After the reaction was completed, the temperature was lowered to room temperature, ultrapure water was added to precipitate the solid, and then the solid obtained by vacuum filtration was carried out. The solid obtained by vacuum filtration was then recrystallized with ethyl acetate to obtain modified phenolphthalein.
[0137] Step (2): Add 273 parts of phenolphthalein monomer, 100 parts of modified phenolphthalein, 170 parts of 2,6-dichlorobenzonitrile, 1000 parts of sulfolane, 160 parts of anhydrous potassium carbonate, and 70 parts of xylene to a reaction vessel, heat to 150°C and hold for 4 hours, then continue heating to 210°C and react for 8 hours to obtain a viscous polymer product.
[0138] Step (3): Add 2500 parts of dimethylacetamide to the solution in step (2) and stir until homogeneous. Under vigorous stirring, pour the solution into a large amount of water to precipitate the product. After filtration, crush the product using a high-speed mixer. Then wash the product with dilute hydrochloric acid and pure water in sequence, and then dry it to obtain low molecular weight modified amorphous polyarylether ketone.
[0139] The calculated ratio of the mass of modified phenolphthalein to the total mass of phenolphthalein monomer and modified phenolphthalein is: 100 / (100+273)*100%=26.8%.
[0140] ② The preparation method of high molecular weight modified amorphous polyarylether ketone is basically the same as that of low molecular weight modified amorphous polyarylether ketone. The difference is that the raw materials for preparing the viscous polymer product in step (2) include 270.3 parts phenolphthalein monomer, 99 parts modified phenolphthalein, 173.7 parts 2,6-dichlorobenzonitrile, 1000 parts sulfolane, 160 parts anhydrous potassium carbonate, and 70 parts xylene.
[0141] The calculated ratio of the mass of modified phenolphthalein to the total mass of phenolphthalein monomer is: 100 / (99+270.3)*100% = 26.8%.
[0142] Comparative Example 4
[0143] The preparation processes of Comparative Example 4 and Example 1 are basically the same. The main difference is that in step S1, 1-chlorobutane is added to the viscous polymer product obtained in step (3) to replace 1-chlorooctane in Example 1.
[0144] Comparative Example 5
[0145] The preparation processes of Comparative Example 5 and Example 1 are basically the same. The main difference is that in step S1, 1-chlorohexadecane is added to the viscous polymer product obtained in step (3) to replace 1-chlorooctane in Example 1.
[0146] Comparative Example 6
[0147] The preparation processes of Comparative Example 6 and Example 1 are basically the same. The main difference is that in step (1), 1-aminopropane is used to replace 3-aminopropyltrimethoxysilane in Example 1 as the raw material for preparing modified phenolphthalein.
[0148] Comparative Example 7
[0149] The preparation processes of Comparative Example 7 and Example 1 are basically the same. The main difference is that in step (2), m-dichlorobenzene is added to replace 2,6-dichlorobenzonitrile in Example 1.
[0150] Experimental Example 1
[0151] The composite resins for producing solvent-based prepregs prepared in Examples 1-6 and Comparative Examples 1-7 were subjected to performance tests, wherein:
[0152] The glass transition temperature of the sample was tested according to GB / T19466.2-2004 "Differential Scanning Calorimetry (DSC) for Plastics - Part 2 - Determination of Glass Transition Temperature".
[0153] The tensile strength of the samples was tested in accordance with GB / T1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics".
[0154] The notched impact strength of the samples was tested according to GB / T1043.2-2018 "Determination of impact properties of simply supported plastic beams - Part 2: Instrumented impact testing";
[0155] The flexural strength of the samples was tested according to GB / T9341-2008 "Determination of Flexural Properties of Plastics".
[0156] The test results are shown in Table 1.
[0157]
[0158]
[0159] As shown in Table 1, the composite resins obtained in Examples 1-3 have glass transition temperatures between 211.4 and 214.3 °C, tensile strength ≥ 90.1 MPa, flexural strength ≥ 130.8 MPa, and notched impact strength ≥ 50.3 KJ / m. 2 .
[0160] Compared to Example 1, the tensile strength, flexural strength and notched impact strength of the composite resin obtained in Example 4 all decreased. This may be because the amount of high molecular weight modified amorphous polyarylether ketone in the system is low, which does not contribute enough to the improvement of the mechanical strength of the composite resin. Therefore, the overall mechanical strength of the obtained composite resin decreased.
[0161] Compared to Example 1, Examples 5 and 6 used a larger amount of high molecular weight modified amorphous polyaryletherketone. Although the tensile strength and flexural strength remained high, the notched impact strength of the resulting composite resin decreased significantly compared to Example 1.
[0162] Compared to Example 1, the tensile strength, flexural strength, and notched impact strength of the composite resin obtained in Comparative Example 1 decreased. This may be because the molecular weight distribution range of the single medium-molecular-weight modified amorphous polyarylether ketone is relatively narrow. Compared with the combination of high-molecular-weight modified amorphous polyarylether ketone and low-molecular-weight modified amorphous polyarylether ketone, the effect of combining mechanical strength and wetting effect is relatively poor. Therefore, the mechanical properties of the obtained composite resin are reduced.
[0163] Compared to Example 1, the composite resin obtained in Comparative Example 2 exhibits an increased glass transition temperature and decreased tensile strength, flexural strength, and notched impact strength. This may be because Comparative Example 2 lacks the large side groups of the amide ring modified with aminosiloxane, resulting in a decreased free volume and molecular chain flexibility of the polymer, and also reduced compatibility with the modified inorganic nanomaterials, thus leading to a decline in the overall performance of the composite resin. In contrast, Comparative Example 6, lacking only siloxane groups, shows slightly higher mechanical properties than Comparative Example 2.
[0164] Compared to Example 1, the glass transition temperature of the composite resin obtained in Comparative Example 3 increased, while its tensile strength, flexural strength, and notched impact strength decreased. This may be because the polymer structure in Comparative Example 3 lacks long-chain alkyl end groups, resulting in a smaller free volume and reduced toughness, thus affecting the glass transition temperature and mechanical properties of the composite resin. The shorter end-capped alkyl segments in Comparative Example 4 resulted in a weaker increase in polymer free volume and toughness compared to Example 1, potentially leading to a decrease in the tensile strength, flexural strength, and notched impact strength of the resulting composite resin. While the longer end-capped alkyl segments in Comparative Example 5 significantly increased the polymer's free volume and toughness, they also caused long chains to become entangled and stacked, negatively impacting the mechanical properties of the resulting composite resin.
[0165] Compared to Example 1, the composite resin of Comparative Example 7 did not contain cyano groups, and its tensile strength, flexural strength, notched impact strength, etc., did not show significant changes, but its performance declined in subsequent applications.
[0166] Application examples
[0167] Prepregs were prepared using the composite resins prepared in Examples 1-6 and Comparative Examples 1-7, and the performance of the prepregs was tested according to GB / T 1447-2005 Tensile Properties Test Method for Fiber Reinforced Plastics. The test results are shown in Table 2.
[0168] Taking prepreg tape as an example, the preparation steps of prepreg tape are as follows:
[0169] Step 1: Dissolve the composite resins obtained in Examples 1-6 and Comparative Examples 1-7 in acetophenone to prepare a 35% (w / w) solution, and pour it into the impregnation tank.
[0170] Step 2: Impregnate T700-12K carbon fiber through a glue bath at a speed of 0.5 m / min, then pass it through a mixed solution of acetone and toluene (the volume ratio of acetone to toluene is 4:1), and then melt the resin by passing it through two drying tunnels at "220℃, 15 min and 350℃, 15 min".
[0171] Step 3: The molten resin is compacted by passing it through a 330°C hot press roller under a pressure of 5MPa to obtain a prepreg tape with a fiber volume fraction of 60%.
[0172] Table 2
[0173] Application Example 1 2180 115 2.10 Application Example 2 2110 108 1.84 Application Example 3 2300 119 2.21 Application Example 4 2000 104 2.25 Application Example 5 2150 117 1.73 Application Example 6 2060 118 1.67 Comparative Application Example 1 1870 93 1.55 Comparative Application Example 2 1690 84 1.32 Comparative Application Example 3 1720 87 1.36 Comparative Application Example 4 1840 94 1.51 Comparative Application Example 5 1800 92 1.45 Comparative Application Example 6 1770 89 1.40 Comparative Application Example 7 1910 99 1.60
[0174] As can be seen from Table 2, the trends in the overall mechanical properties of the obtained prepreg tape, including tensile strength, tensile modulus, and elongation at break, are consistent with the trends in the mechanical properties of the composite resin. Although the composite resin prepared in Comparative Example 7 has superior properties, the prepreg tape prepared using it has significantly inferior properties compared to Application Examples 1-6. This may be because the active cyano group has strong polarity, which can enhance the bonding ability with other components (such as carbon fibers) while maintaining the polymer's high-temperature resistance and toughness.
[0175] This invention illustrates the detailed process equipment and process flow through the above embodiments. However, this invention is not limited to the detailed process equipment and process flow described above, meaning that this invention does not necessarily depend on the detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials, structural changes, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this invention.
[0176] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0177] The above embodiments are only for illustrating the technical concept and features of the present invention. Their purpose is to enable those skilled in the art to understand the content of the present invention and implement it. They should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A composite resin for solvent-based prepreg production, characterized in that, The raw materials for preparing composite resins, by weight, include: 35-145 parts of modified amorphous polyaryletherketone; 8-35 parts polycarbonate; 0.5-6 parts of modified inorganic nanomaterials; Antioxidant 0.1-1 part; The modified amorphous polyaryletherketone includes high molecular weight modified amorphous polyaryletherketone and low molecular weight modified amorphous polyaryletherketone. The mass ratio of high molecular weight modified amorphous polyarylether ketone to low molecular weight modified amorphous polyarylether ketone in the modified amorphous polyarylether ketone is 3-30:
1. The high molecular weight modified amorphous polyarylether ketone has an average molecular weight of 20,000-40,000; the low molecular weight modified amorphous polyarylether ketone has an average molecular weight of 5,000-10,000. The modified amorphous polyarylether ketone is prepared as follows: Step (1): Add the side chain agent to the phenolphthalein monomer, heat to 160-200℃ and react for 30-60 h to obtain modified phenolphthalein. Step (2): Add modified phenolphthalein, phenolphthalein monomer, 2,6-dichlorobenzonitrile, sulfolane, anhydrous potassium carbonate, and xylene to the reaction vessel, heat to 140-160℃ and hold at that temperature for 3-5 hours, then continue heating to 200-220℃ and react for 6-10 hours to obtain a viscous polymer product. Step (3): Add haloalkanes to the product obtained in step (2), heat to 190-210℃, stir for 1.5-3h, purify, and obtain modified amorphous polyarylether ketone. The side chain agent in step (1) is at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, diaminopropylpolydimethylsiloxane, and aminopropyl-terminated polydimethylsiloxane. The alkyl chain length of the haloalkane in step (3) is C7-C10.
2. The composite resin according to claim 1, characterized in that, The raw materials for preparing the composite resin include: 42-130 parts of modified amorphous polyarylether ketone, 12-30 parts of polycarbonate, 1.5-4.5 parts of modified inorganic nanomaterials, and 0.1-0.3 parts of antioxidant.
3. The composite resin according to claim 1, characterized in that, The mass ratio of the high molecular weight modified amorphous polyaryletherketone to polycarbonate is 2-6:
1.
4. The composite resin according to claim 1, characterized in that, The mass ratio of the high molecular weight modified amorphous polyarylether ketone to the low molecular weight modified amorphous polyarylether ketone is 6-15:
1. The mass ratio of the high molecular weight modified amorphous polyarylether ketone to polycarbonate is 3-4:
1.
5. The composite resin according to claim 1, characterized in that, In step (1), the mass ratio of phenolphthalein monomer to side-chain agent is 1:1.5-3; The amounts of each substance used in steps (2) and (3) are as follows: 260-300 parts of phenolphthalein monomer, 50-130 parts of modified phenolphthalein, 140-200 parts of 2,6-dichlorobenzonitrile, 800-1300 parts of sulfolane, 120-290 parts of anhydrous potassium carbonate, 20-100 parts of xylene, and 5-13 parts of halogenated hydrocarbons; The modified phenolphthalein accounts for 10-30% of the total mass of phenolphthalein monomer and modified phenolphthalein.
6. The composite resin according to claim 1, characterized in that, The modified inorganic nanomaterial is a pretreated inorganic powder modified with a silane coupling agent; The silane coupling agent is at least one of KH550, KH560, and KH570; The pretreated inorganic powder is the product obtained by activating inorganic powder at 300-600℃ for 3-7 hours; The inorganic powder is at least one of silicon dioxide, montmorillonite, bentonite, and kaolinite. The mass ratio of the silane coupling agent to the pretreated inorganic powder is 1:20-30.
7. A method for preparing the composite resin according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Mix high molecular weight modified amorphous polyaryletherketone, low molecular weight modified amorphous polyaryletherketone, polycarbonate, modified inorganic nanomaterials, and antioxidant evenly to obtain a mixture; S2. Add the mixture to a twin-screw extruder, extrude and granulate to obtain modified particles; S3. The modified particles are cryogenically pulverized to a particle size of 50-100 μm to obtain a composite resin.
8. The method for preparing the composite resin according to claim 7, characterized in that, In step S2, extrusion granulation is performed at 200-310°C; In step S3, the freezing temperature is -120℃ to -80℃.
Citation Information
Patent Citations
Phenolphthalein polyaryletherketone polymer and end capping method
CN116515100A
Resin containing cyano phenolphthalein polyaryl ether nitrile ketone, prepreg and high-toughness composite material
CN117659627A
